Анализ финансирования программ социально- экономического развития регионов из местных бюджетов - Abrayev, Farrukh (THE INNOVATION ECONOMY, 2024)
The article discusses the formation of fi nancing for regional socio-economic development projects from local budgets, general, fi nancial and fi nancial-organizational organizations, as well as the organization of fi nancing of regional socio-economic development programs from local budgets, mechanisms for controlling fi nancing from budgetary funds.